2020
DOI: 10.1002/hon.2807
|View full text |Cite
|
Sign up to set email alerts
|

Humanized anti‐CD19 chimeric antigen receptor‐T cell therapy is safe and effective in lymphoma and leukemia patients with chronic and resolved hepatitis B virus infection

Abstract: Chimeric antigen receptor‐T (CAR‐T) cell therapy is a promising treatment for CD19+ B‐cell malignancies. However, elimination of B cells by anti‐CD19 CAR‐T cells may lead to the reactivation of hepatitis B virus (HBV) and related hepatitis in patients with HBV infection. This study aims to evaluate the safety and efficacy of humanized anti‐CD19 CAR‐T (hCAR‐T) therapy in B‐cell malignancies with HBV infection. Twenty relapsed/refractory (r/r) diffuse large B‐cell lymphoma (DLBCL) and acute lymphoblastic leukemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Han et al reported a case of HBV reactivation in eight patients with multiple myeloma and resolved HBV infection receiving CAR-T cells targeting BCMA (18). In contrast, three case series reported no reactivation among HBsAg−/HBcAb+ patients treated with single CART19 cell therapy (19)(20)(21). In two of the series, the proportion of patients with positive HBsAb was particularly high (90.9 and 85%, respectively) and some of them received prophylactic nucleotide therapy.…”
Section: Discussionmentioning
confidence: 98%
“…Han et al reported a case of HBV reactivation in eight patients with multiple myeloma and resolved HBV infection receiving CAR-T cells targeting BCMA (18). In contrast, three case series reported no reactivation among HBsAg−/HBcAb+ patients treated with single CART19 cell therapy (19)(20)(21). In two of the series, the proportion of patients with positive HBsAb was particularly high (90.9 and 85%, respectively) and some of them received prophylactic nucleotide therapy.…”
Section: Discussionmentioning
confidence: 98%
“…In the published cases, [4][5][6] patients with positive HBV DNA and HBsAg have been started on entecavir no later than at initiation of lymphodepleting chemotherapy, in line with the recommendations for HBV in hematological diseases in general. 11 The ideal time for discontinuation is not known and will depend upon the level of cytopenia and the patient's status.…”
mentioning
confidence: 82%
“…3 Case studies have described safe administration of CAR T-cells to adult patients with chronic HBV receiving antiviral prophylaxis. [4][5][6] We describe the first case of acute HBV infection in a child undergoing CAR T-cell therapy.…”
mentioning
confidence: 99%
See 2 more Smart Citations